A case report about oligodendrogliomas of the fourth ventricle. Issue 17 (April 2018) - Gai, Xiujuan; Li, Shaomei; Wei, Yumei; Yu, Shuhua
Abstract: Rationale: Oligodendrogliomas are usually located in the frontal, parietal and the temporal lobe, with the ones in the fourth ventricle quite rare. Hence we want to introduce a case about the rare disease. Patient concerns: An eight-year old boy complained of progressive headache, dizziness and vomit for about 2 months. Then the slight ataxia was found by the physical examinations, with no sensory disturbances and other motor disturbances. Diagnoses: Abnormal signals on the fourth ventricle were found by the preoperative brain computed tomography (CT) scan and magnetic resonance imaging (MRI) scan. So the patient accepted a gross total resection of the lesion with pathologically confirmed oligodendroglioma. Interventions: Radiotherapy was then delivered in 27 fractions at 2Gy per fraction after the operation, with one fraction daily for five days weekly. No other therapies were used for the patient. Outcomes: The brain MRI was used for follow-up every three months until now when he has finished all therapies for more than one year. No progressive behaviors (for example, headache, dizziness, vomit and other symptoms about cerebellar tonsillar hernia) or images have been presented. And the follow-up will be continued. Lessons: Although oligodendrogliomas are usually located in the frontal lobe, with the ones of fourth ventricle extremely rare, they must be kept in mind all times. Treatments applied to our case may be provided as a reference for clinicians. Furthermore, the maximal range of resection, histologically proved oligodendroglioma and the 1p/19q loss of heterozygosity are associated with favorable prognosis.